TEACHING ENGLISH AS A LOCAL CONTENT IN THE FOURTH GRADE STUDENTS OF SDN BOGOREJO MERAKURAK TUBAN - Ali Fauzi (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2020)
English is an international language used by the people all over the world, therefore to master English-speaking, writing, reading and listening especially for educated people is a must. Knowing this, Indonesian government prepares early and declares that English should be taught as compulsory local content subject in the Elementary school. It is good idea because very young children are easily able to understand English. The government introduces English as a compulsory local content subject taught since they are in the Elementary school throughout Indonesia in order that after they graduate from Elementary school, they then continue to learn it until they graduate from University and have the mentioned skills. That is why, the researcher is interested in conducting the English teaching research at SDN Bogorejo Merakurak Tuban by choosing the title “Teaching English as a Local Content in the Fourth Grade Students of SDN Bogorejo Merakurak Tuban. The researcher wants to know and describes how she teaches them, what she does, what materials she prepares, and what is the students attitude towards the teaching of English. The result of this study is expected to be able to give an important contribution on the development of teaching English strategy that can support the development of teaching and learning English. This research is qualitative research in form of case study. The researcher takes only one class-the fourth class students of SDN Bogorejo Merakurak Tuban as the object of research. The approach of the research is phenomenological approach in which the researcher observes and interprets the facts based on the phenomena in the classroom during the teaching of English although it is may be subjective. The researcher also finds the data from many literatures to get theory and and principle as the secondary data used as a means of analyzing it. The method of research he uses is descriptive-qualitative which means that he just describes his finding on the teaching of English. The subject of the research is the students of four class of SDN Bogorejo Merakurak Tuban and the number of it is 24 students. The result of the research is that teacher at SDN Bogorejo Merakurak Tuban has taught the students successfully. The Researcher does the research since the students get into the classroom and study through the model of Luring since the first week of September 2020. The teacher prepares the material well and applied many kinds of strategy to motivate students to learn English diligently. After studying English, the students now become so enthusiastic that they study by themselves at home because of their own will.